Keloidal-like local recurrence after infiltrating adenosquamous breast carcinoma with stromal-overgrowth mimicking a benign skin lesion - Stolnicu, Simona; Giurgi, Alexandra; Naznean, Adrian; Podoleanu, Cristian; Chiriac, Anca (Polish Journal of Pathology, 2018)
We present a very rare case of an adenosquamous infiltrating breast carcinoma with sarcomatous stromal overgrowth of hypocellular collagenised type, which subsequently developed local recurrence, mistaken for a benign skin lesion due to bland keloid-like morphological appearance. All the histological, immunohistochemical, and clinical features must be taken into consideration when distinguishing between a benign skin lesion and a local recurrence of a rare subtype of breast carcinoma.